The locked psychiatric ward: Hotel or detention camp for people with dual diagnosis. (2013) - Terkelsen, Toril Borch; Larsen, Inger Beate
Abstract : Background: The concepts of autonomy and liberty are established goals in mental health care; however, involuntary commitment is used towards people with mental health and substance abuse problems (dual diagnosis). Aims: To explore how patients and staff act in the context of involuntary commitment, how interactions are described and how they might be interpreted. Method: Ethnographic methodology in a locked psychiatric ward in Norway. Results: Two parallel images emerged: (a) The ward as a hotel . Several patients wanted a locked ward for rest and safety, even when admission was classified as involuntary. The staff was concerned about using the ward for real treatment of motivated people, rather than merely as a comfortable hotel for the unmotivated. (b) The ward as a detention camp . Other patients found involuntary commitment and restrictions in the ward as a kind of punishment, offending them as individuals. Contrary, the staff understood people with dual diagnoses more like a generalized group in need of their control and care. Conclusion: Patients and staff have different perceptions of involuntary commitment. Based on the patients' points of view, mental health care ought to be characterized by inclusion and recognition, treating patients as equal citizens comparable to guests in a hotel.